PERAN GURU PROFESIONAL SEBAGAI FASILITATOR DAN KOMUNIKATOR DALAM KEGIATAN BELAJAR MENGAJAR - Arfandi Arfandi; Mohamad Aso Samsudin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2021)
the role of professional teachers in carrying out activities as educators obligate to have a capability in the learning plan, performing the learning activities, and evaluate learning outcomes. Professional teachers have to own competence, both personal competence, pedagogical competence, and social competence. There are several important roles for a professional teacher that are as a leader, guide, supervisor, counselor, expeditor, motivator, facilitator, and communicator. The role of the teacher as a facilitator to provide great service with the aim of providing convenience to students in teaching and learning activities, to realize teachers as facilitators, teacher needs to provide various learning resources and learning media that are relevant as well as make active learning, innovative, creative and fun. Whereas, the teacher as a communicator in teaching and learning activities that the relationship between the teacher and students is not only "top-down" but a partnership, through the partnership model the teacher will act as a guide and companion in teaching and learning activities so that created a delight and democratic learning atmosphere.